WHIRLY1 of Barley and Maize Share a PRAPP Motif Conferring Nucleoid Compaction. (11th November 2021) - Oetke, Svenja; Scheidig, Axel J; Krupinska, Karin
Abstract: WHIRLY1 in barley was shown to be a major architect of plastid nucleoids. Its accumulation in cells of Escherichia coli coincided with an induction of nucleoid compaction and growth retardation. While WHIRLY1 of maize had similar effects on E. coli cells, WHIRLY1 proteins of Arabidopsis and potato as well as WHIRLY2 proteins had no impact on nucleoid compaction in E. coli . By mutagenesis of HvWHIRLY1 the PRAPP motif at the N-terminus preceding the highly conserved WHIRLY domain was identified to be responsible for the nucleoid compacting activity of HvWHIRLY1 in bacteria. This motif is found in WHIRLY1 proteins of most members of the Poaceae family, but neither in the WHIRLY2 proteins of the family nor in any WHIRLY protein of eudicot species such as Arabidopsis thaliana . This finding indicates that a subset of the monocot WHIRLY1 proteins has acquired a specific function as nucleoid compacters by sequence variation in the N-terminal part preceding the conserved WHIRLY domain and that in different groups of higher plants the compaction of nucleoids is mediated by other proteins.